Edukasi dan Aksi Pencegahan Anemia pada Remaja Melalui Konsumsi Tablet Tambah Darah - Adhayanti, Ida; Fachriani, Zakia; Arma, Armadhan; Hasanah, Firma Nur; Ramadhani, Nur Fadiah; Marwah, Siti (Jurnal Pengabdian Kefarmasian, 2024)
Preventing Anemia Through Regular Iron Supplement IntakeAnemia is a significant public health issue, particularly among adolescent girls, with a high prevalence in Makassar. Low hemoglobin levels and a lack of understanding about healthy dietary practices are the main causes of anemia, requiring effective interventions to prevent and address this condition. Objective: This community service activity aimed to enhance the knowledge of adolescent girls about anemia, the importance of consuming iron supplements, and preventive measures through community-based education. Methods: The activity was conducted using interactive lectures supported by presentation media, Q&A sessions to clarify misunderstood information, a group iron supplement consumption practice, and the distribution of educational leaflets as additional guidelines. Evaluation was carried out using pre-test and post-test questionnaires to assess participants' knowledge improvement. Outputs: The results demonstrated a significant increase in participants’ knowledge, with 43.33% categorized as having good knowledge before the session, rising to 90% after the session. Participants also showed high enthusiasm during the activity through active engagement in discussions and direct practice. Conclusion: This educational program successfully improved adolescent girls' knowledge and awareness of anemia and its prevention, motivating them to adopt preventive measures through regular consumption of iron supplements.Remaja perempuan, dengan prevalensi yang cukup tinggi di Kota Makassar. Rendahnya kadar hemoglobin dan kurangnya pemahaman tentang pola makan sehat menjadi faktor utama penyebab anemia, sehingga diperlukan intervensi yang tepat untuk mencegah dan mengatasinya. Tujuan Kegiatan: Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan remaja perempuan tentang anemia, pentingnya konsumsi tablet tambah darah, dan langkah-langkah pencegahan melalui edukasi berbasis komunitas. Metode Kegiatan: Kegiatan dilaksanakan dengan metode ceramah interaktif menggunakan media presentasi, sesi tanya jawab untuk mengklarifikasi informasi yang kurang dipahami, praktik minum tablet tambah darah bersama, serta pembagian leaflet edukasi sebagai panduan tambahan. Evaluasi dilakukan melalui kuesioner pre-test dan post-test untuk mengukur peningkatan pengetahuan peserta. Capaian Luaran: Hasil kegiatan menunjukkan peningkatan signifikan pada tingkat pemahaman peserta, dengan 43,33% peserta berada dalam kategori pengetahuan baik sebelum penyuluhan, meningkat menjadi 90% setelah penyuluhan. Peserta juga menunjukkan antusiasme tinggi selama kegiatan melalui partisipasi aktif dalam diskusi dan praktik langsung. Kesimpulan: Penyuluhan ini berhasil meningkatkan pengetahuan dan kesadaran remaja perempuan tentang anemia dan pencegahannya, serta memotivasi mereka untuk menjalankan langkah pencegahan melalui konsumsi tablet tambah darah secara rutin.